Copernicus Sentinel opportunities using field spectroscopy to support deep man-made infrastructures in Cyprus - Melillos, George; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2018)
Satellite remote sensing is considered as an increasingly important technology for military intelligence. It can be applied to a wide range of military applications, as shown from various researchers. However, there is a great need to integrate information from a variety of sources, rendered available at different times and of different qualities using remote sensing tools. This paper provides a solid methodology to support Sentinel remote sensing detection of deep man made infrastructures in Cyprus using field spectroscopy. A number of vegetation indices such as the Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR), Difference Vegetation Index (DVI) and Optimized Soil Adjusted Vegetation Index (OSAVI), combined with other in-band algorithms were utilized for the development of a vegetation index-based procedure aiming at the detection of underground military structures. The measurements were taken at the following test areas: (a) vegetation area covered with the vegetation (barley), in the presence of an underground military structure (b) vegetation area covered with the vegetation (barley), in the absence of an underground military structure. The test areas were identified, analyzed and modelled under different scenarios. Sentinel-2A is a promising tool for detecting underground structures.
Keywords: Military underground structures; NDVI; Satellite; Sentinel 2A; Spectroscopy; Vegetation indices